Formulation and In-Vitro Characterization of Oral Controlled Release Microspheres of Itopride Hydrochloride - Anuradha S. Khedkar,; Dr. Nishan N. Bobade,; Nishant P. Deshmukh,; Mahendra A.Patil, (Asian Journal of Pharmaceutical Research and Development, 2025)
The aim of this work was to design a controlled release drug delivery system for the prokinetic agent Itopride Hydrochloride. Itopride Hydrochloride was encapsulate using ethyl cellulose and HPMC K 100 M by solvent evaporation method and physiochemical properties of formulation were characterized. The obtained microsphere showed good flow properties with angle of repose, bulk density, tapped density, Carr’s index, Hausner’ratio was found to be 30096’±0.45 to34099’±0.12, 0.390±0.41g/ml to 0.423±0.55 g/ml, 0.438±0.23 g/ml to 0.484±0.88 g/ml, 10.72±0.43% to 15.25±0.38%,1.12±0.11 to 1.18±0.45 respectively. Using solvent evaporation method, microspheres percentage yield was found to be 78±0.77%-88.18±0.24%.The percentage entrapment efficiency of various formulations was found to be 80.72±0.99% to 91.72±0.12%. As concentration of polymer increases, it retards the release of drug upto 24 hours. As concentration of HPMC K100M increases drug release time increases. Optimized formulation E-9 contain 200 mg Itopride HCL, 450 mg of HPMC K 100M and 450 mg of Ethyl Cellulose. The result of formulation E-9 for Angle of Repose, Bulk Density, Tapped Density, Carr’s Index, Hausners Ratio, Percent Yield, Drug Entrapment Efficiency, percent Cumulative Drug Release, Zeta Potential, Particle Size were 30096’±0.45, 0.408±0.77, 0.457±0.23, 10.72±0.43, 1.12±0.1, 88.18±0.24%, 91.72±0.12%, 80.05±0.5%, 21.72mV, 747.7 µ respectively. It was concluded that the prepared controlled release microspheres of Itopride Hydrochloride may prove to be potential candidates for safe and effective controlled drug delivery.